Analisis Konflik Batin Karen Horney pada Tokoh Utama dalam Novel Pukul Setengah Lima Karya Rintik Sedu - Arni Yuniar Prastika; Wawan Hermawan; Rani Jayanti (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
This study aims to analyze the tendency of moving toward people in the main character of the novel Pukul Setengah Lima by Rintik Sedu using Karen Horney’s psychoanalytic theory. The main character exhibits behaviors that reflect a neurotic need for affection, approval, and protection through submissiveness, self-sacrifice, and emotional dependence on others. A descriptive qualitative approach is employed, using content analysis of excerpts from the novel. The findings reveal that the tendency to move toward others serves as a psychological response to social anxiety rooted in unresolved inner conflicts and emotional insecurity from the past. This pattern of unbalanced interpersonal relationships acts as a defense mechanism to gain a sense of safety in social life. The study contributes to a deeper understanding of psychological dynamics in contemporary Indonesian popular literature and enriches the field of literary psychology.